Annular‐ring slot antenna designs with circular polarization radiation. Issue 4 (6th November 2014) - Sim, C. Y. D.; Weng, W. C.; Chang, M. H.; Chen, B. Y.
ABSTRACT: The design of a microstrip‐fed annular‐ring slot antenna (ARSA) with circular polarization (CP) radiation is initially studied. To obtain CP radiation with broad 3‐dB axial ratio (AR) bandwidth that can cover the WiMAX 2.3 GHz (2305–2320 MHz, 2345–2360 MHz) and WLAN 2.4 GHz (2400–2480 MHz) bands, a novel technique of extending an inverted L‐shaped slot from the bottom section of the annular‐ring is proposed. To suppress the harmonic modes induced by the CP ARSA, the technique of integrating a defected ground structure into the annular‐ring slot is further introduced. From the measured results, 10‐dB impedance bandwidth and 3‐dB AR bandwidth of 44.86 and 9.68% were achieved by the proposed harmonic suppressed CP ARSA. Furthermore, average gain and radiation efficiency of ∼4.7 dBic and 71%, respectively, were also exhibited across the bands of interest. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:337–345, 2015.